TEOLOGI ABSENSIA : SEBUAH TAWARAN - Bawono, Haryo Tejo (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2007)
Referring back to the age-old tradition of Negative Theology and combining it with deconstructive 'Heuristic Way' of French Postmodern Philosophico-Theology , this article seeks to reiterate the centrality of 'Absence' vis-à- vis 'Metaphysics of Presence'. Theology of absence is offered as a middleway between affirmative and negative theology by incorporating some basic ideasof Derrida, Jean-Luc Marion, Michel Henry, Levinas and Marc C. Tylor. In the final analysis, it is 'Life' itself that is to be the focus of theology.